Effect Of Audit Tenure, KAP Rotation And Audit Fee On Audit Quality - Haninda Condrowati; Nursiam, Nursiam (Jurnal Ekonomi, 2024)
Audit is a process that is conducted independently to ensure that the information used in decision making is complete, accurate, and unbiased.  The importance of audit quality for users of financial statements became the center of attention for this study. Auditors who are independent parties are expected to protect the interests of shareholders and creditors. This study aims to examine the effect of audit tenure, Kap rotation and audit fee on audit Quality. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange for the period 2020-2022. Sampling was carried out using purposive sampling method to obtain a sample of 75 companies with an observation period of 3 years so that the data obtained as many as 225 data. The method of analysis of this study using logistic regression analysis with the help of SPSS 25. The results showed that the audit tenure and audit fee have an influence on the quality of the audit, while the rotation of the hood does not affect the quality of the audit.